Features Logistics Customs Warehouses in the Integration of the World Economy and the Globalization of Business - Kalinicheva, Valentina; Dmitriev, Sergey; Drigo, Mikhail; Kazimirova, Natalia; Nikitina, Alla; Igolnikova, Inna (International Review of Management and Marketing, 2016)
Using logistic approach in the management of export-import trade flows has acquired particular urgency at the present stage of economic development. This is due to the intensification and expansion of foreign economic relations of the state, and the dynamic expansion of the horizontal ties between economic entities of the partner countries. Increased opportunities to improve cooperation by enhancing the economic independence and initiative of intermediaries and transport organizations, improving their contractual relations and mutual economic incentives. Russia is in a better position the intersection of the European transport corridors, which is a prerequisite for the possible establishment of a full-fledged participant in the process of the international movement of goods and services. The implementations of these prospects are largely dependent on the activity of the customs authorities of the country. The introduction of high-quality customs service, the use of effective and innovative technologies in the customs warehousing design and control, is an important characteristic of the customs activity. That is why more attention should be paid to the study of the experience of using the methods of the organization of the logistics system of customs clearance and control. Keywords: logistics, bonded warehouses, transit, customs area JEL Classifications: F6, P3